ANALISIS PENGAKUAN PENDAPATAN DAN BEBAN BERDASARKAN PSAK NO.27 PADA KSP SYARIAH AL-IKHLAS KABUPATEN TAKALAR - Suarni, Agusdiwana; Sulastri, Sulastri (Universitas Muhammadiyah Makassar, 2018)
The research aims to find out the level of compatibility between the recognition of income and the burden applied by KSP Syari'ah Al-Ikhlas with the provisions in PSAK No.27. The data processed is an acknowledgment of income and burden obtained from the financial statements of KSP Syaria'ah AL-Ikhlas. The data analysis technique used in this study is quantitative descriptive analysis. The source of data used in this study is the primary data in the form of secondary data that is data that has been further processed, namely the report of residual income from the results of business and the brief history of the establishment of KSP Syari'ah Al-Ikhlas. ah Al-Ikhlas applies the cash basis method, not in accordance with PSAK No. 27 because according to PSAK No.27 the method applied is at the calculation of business results (accrual basis) which is expected profit and burden set at the time the transaction is executed. In the recognition of the burden on KSP Syaria'ah AL-Ikhlas apply the accrual basis method that has been in accordance with PSAK No.27. However, in its presentation of the results of the business results of KSP Syaria'ah AL — Ikhlas has not separated between the business burden and the burden of cooperation with PSAK No. 27.Keywords: PSAK No.27, KSP Syari’ah Al-Ikhlas, Takalar